Deubiquitinase PSMD14 promotes ovarian cancer progression by decreasing enzymatic activity of PKM2. Issue 12 (25th August 2021) - Sun, Tianshui; Liu, Zhuonan; Bi, Fangfang; Yang, Qing
Abstract : Dysregulation of deubiquitination has been reported to contribute to carcinogenesis. However, the function and mechanism of deubiquitinating enzyme 26S proteasome non‐ATPase regulatory subunit 14 (PSMD14) in the progression of ovarian cancer (OV), the deadliest gynecological cancer, still remains to be characterized. The present study demonstrated that PSMD14 was overexpressed in OV tissues and its higher levels correlated with a higher International Federation of Gynecology and Obstetrics (FIGO) stage in OV patients. A high level of PSMD14 expression was related to poor survival in OV patients. Knockdown and overexpression experiments elucidated that PSMD14 stimulated OV cell proliferation, invasion, and migration in vitro . Repression of PSMD14 suppressed OV tumor growth in vivo . PSMD14 inhibitor O‐phenanthroline (OPA) effectively attenuated malignant behaviors of OV cells in vitro and OV tumor growth in vivo . Mechanistically, we uncovered that PSMD14 was involved in post‐translational regulation of pyruvate kinase M2 isoform (PKM2). PSMD14 decreased K63‐linked ubiquitination on PKM2, downregulated the ratio of PKM2 tetramers to dimers and monomers, and subsequently diminished pyruvate kinase activity and induced nuclear translocation of PKM2, contributing to aerobic glycolysis in OV cells. Collectively, our findings highlight the potential roles of PSMD14 as a biomarker and therapeutic candidate for OV. Abstract : PSMD14 decreases K63‐linked ubiquitination on PKM2 and downregulates the ratio of PKM2 tetramers to dimers and monomers. Subsequently, this diminishes pyruvate kinase activity and induces nuclear translocation of PKM2 as well as transcription of downstream genes, contributing to aerobic glycolysis in ovarian cancer cells and progression of ovarian cancer.